Strengthening Family Resilience through Financial Management Education in Facing the Covid-19 Pandemic - Suci Megawati; Muhammad Farid Ma’ruf; Eva Hany Fanida; Fitrotun Niswah; Trenda Aktiva Oktariyanda (Journal La Bisecoman, 2020)
This research aimed at examining how the economic impact of households in the midst of the Covid-19 pandemic and how the solution focuses on the accuracy of household financial management. The study employs R&D (Research and Development. Sampling is done using the incidental sampling technique, formulated the number of community samples incidentally spread over 22 districts in Sidoarjo Regency. Data collection techniques using primary data, in the form of a questionnaire in google form format as a tool in collecting data in the field and secondary data in the form of documentation and literature study. The results of the study show that business turnover by 65 percent, a decrease in income by 60 percent, layoffs by 55 percent, limited job vacancies as much as 60 percent.